Online shopping orientation among tourism students in UiTM / Diyana Abd. Rohman, Norazuwaaireen Othman and Zafirah Noorsharifuzan - Abd. Rohman, Diyana; Othman, Norazuwaaireen; Noorsharifuzan, Zafirah (2015)
Consumer behavior is a specific cultural and it is still unclear whether the findings of the reports about the consumer online purchase intention in foreign countries can be implemented directly in a cultural of UiTM. In order to fulfill the gap in the literature regarding the consumer online purchase intention, the current study will examine the consumer online purchase intention among students in UiTM (Ling et al, 2010). So, this attention of this study is to analyze the consumer online behavior towards online purchase intention among tourism students in UiTM. According to Ling et al. (2010) state that web shopping can be more risky and the foreign countries culture, they do not necessarily focus on the customer behavior. In Malaysian culture, the web retailers still focus on the traditional on the consumer behavior that contribute to the online purchase intention.